Is Metro Vancouver ready to reduce their waste? An evaluation of returnable/reusable container programs - Davis, Shawn; Heacock, Helen; BCIT School of Health Sciences, Environmental Health (BCIT Environmental Public Health Journal, 2021)
As the interest in delivery and take-out meals increases, so too does the amount of food packaging that ends up in the landfill. Programs and incentives are already in place and continue to be adjusted to encourage the reduced reliance on these materials. This study focuses on returnable and recyclable container programs (RRCP) and British Columbian’s interest in these programs for Metro Vancouver.